(3ebGdGJ aj GdcjejGAs
(3ChdgG (B:s
(3HGH JOHjQ GdQUGU hgh GdeThi CeG SbjI gPG GdLSO ajchf HLejY eG PcQfG ai SbjGJ RMd s
(3BNQgG (B:s
(3UfYg LjOI ef GdJfO GdChd GdeOchQ jDNP YTQI eKGbjd eSc eSMhb hjLeY aJGjd hjbWY HGdScjf HGQc Gddg ajc hYdjc s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B8s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs